2017
DOI: 10.1007/s11695-017-2902-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Micronutrient Deficiency in Patients with Morbid Obesity Before Bariatric Surgery

Abstract: Our data show a high prevalence of micronutrient deficiency in patients with morbid obesity preoperatively and emphasize the importance of exact preoperative evaluation and adequate substitution as well as postoperative surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 26 publications
3
57
0
4
Order By: Relevance
“…Vitamin D deficiency defined based on the presence of low serum 25-hydroxyvitamin D (25OHD) levels is very frequent in obesity and was reported to occur in 55-97% (169,170). However, it is important to understand the mechanisms underlying the lower 25OHD levels in obesity and whether this indicates a clinically significant vitamin D deficiency.…”
Section: Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D deficiency defined based on the presence of low serum 25-hydroxyvitamin D (25OHD) levels is very frequent in obesity and was reported to occur in 55-97% (169,170). However, it is important to understand the mechanisms underlying the lower 25OHD levels in obesity and whether this indicates a clinically significant vitamin D deficiency.…”
Section: Reasoningmentioning
confidence: 99%
“…Thus, vitamin D deficiency to the extent that will drive an increase in bone turnover or decrease bone mineral density is clinically relevant. The prevalence of secondary hyperparathyroidism (sHPT) related to vitamin D deficiency in obesity was reported to be over 20% (169,178) and increased up to 71% depending on vitamin D status (171), while the threshold for parathyroid stimulation can be widely variable (179,180). In addition to disturbances in the vitamin D -calcium homeostasis, obesity may involve other mechanisms affecting PTH regulation that are incompletely understood.…”
Section: Reasoningmentioning
confidence: 99%
“…Several studies have observed the micronutrient deficiencies among BS candidates and reported that these patients displayed at least one vitamin or mineral baseline deficit [40,41,[49][50][51]. Table 1 presents the most common nutritional deficiencies and their prevalence documented in patients evaluated before BS.…”
Section: Micronutrient Status Of Bs Candidates: Impact On Gmmentioning
confidence: 99%
“…Micronutrient deficiencies are frequently reported after RYGB and VSG [9,51,96,97], with an incidence as great as 50% in mid-and long-term follow-ups [86]. The underlying variables associated to postoperative vitamin and mineral deficiencies are both surgery-and patient-related ( Figure 3 Micronutrient deficiencies are frequently reported after RYGB and VSG [9,51,96,97], with an incidence as great as 50% in mid-and long-term follow-ups [86]. The underlying variables associated to postoperative vitamin and mineral deficiencies are both surgery-and patient-related ( Figure 3) [98].…”
Section: Pathogenesis Of Micronutrient Deficiencies After Bsmentioning
confidence: 99%
“…Furthermore, women who are obese are more likely to have children who are obese (Oestreich & Moley 2017), perpetuating health problems from generation to generation. There is evidence that obese individuals are deficient in micronutrients (Costa et al 2018;Krzizek et al 2017;Stankowiak-Kulpa et al 2017).…”
Section: Introductionmentioning
confidence: 99%